4n=5(n+1)-3(n-1)

Simple and best practice solution for 4n=5(n+1)-3(n-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4n=5(n+1)-3(n-1) equation:


Simplifying
4n = 5(n + 1) + -3(n + -1)

Reorder the terms:
4n = 5(1 + n) + -3(n + -1)
4n = (1 * 5 + n * 5) + -3(n + -1)
4n = (5 + 5n) + -3(n + -1)

Reorder the terms:
4n = 5 + 5n + -3(-1 + n)
4n = 5 + 5n + (-1 * -3 + n * -3)
4n = 5 + 5n + (3 + -3n)

Reorder the terms:
4n = 5 + 3 + 5n + -3n

Combine like terms: 5 + 3 = 8
4n = 8 + 5n + -3n

Combine like terms: 5n + -3n = 2n
4n = 8 + 2n

Solving
4n = 8 + 2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-2n' to each side of the equation.
4n + -2n = 8 + 2n + -2n

Combine like terms: 4n + -2n = 2n
2n = 8 + 2n + -2n

Combine like terms: 2n + -2n = 0
2n = 8 + 0
2n = 8

Divide each side by '2'.
n = 4

Simplifying
n = 4

See similar equations:

| 4n+1=4n-5 | | 2m+23=-7+7m | | x+4/3=x | | 3(4l+1)=27 | | (5x+3)2-2(6x+10)= | | 5k+3-2k=-57 | | x2/3=w-y | | -j+2=12 | | 3/5i-2=7 | | 4/5h=16 | | 216=1.5a+a | | 216=2.5a+a | | 0.5a+a=1.5a | | (X^2+6)((x+8)/x)(-7) | | 216=0.5a+a | | (6x+9)^1/5=(-5-4x)^1/5 | | 216=0.5xa+a | | 9x^2+55=0 | | [x+2]-3X=5 | | x(2x-28)+90=0 | | 54=9l-6w | | 50x=(10+.333x)*85 | | -7n-16=4+17 | | 2x+17x=13x | | x+x+2/4=189.5 | | 3x^2-5=7 | | -6y+4(y+2)=24 | | log[5](x+18)-log[5](x-6)=2 | | 2-3b=7+12 | | 2(x+3)+3(x-4)=5(x-1)-1 | | 1-1/4=10 | | 17-x=1/3*15+6 |

Equations solver categories